Fungsi dan Nilai Tradisi Hajat Lembur di Tatar Karang Priangan Tasikmalaya Jawa Barat - Samson CMS; N Rinaju Purnomowulan (Pascasarjana ISBI Bandung, 2019)
The purpose of this research is to determine the function and traditional values of hajat lembur in the life tatar Karang Priangan society. The research method used is an ethnographic study. The result shows that the transfer of knowledge on how to care for nature and how humans communicate with the universe, namely the harmonization of culture and religion, become a collective identityin this ethics of life. Hajat lembur tradition is a media culture and local wisdom in controlling the people’s lives. The external perception which is not in harmony with the traditions is thought to be one of the causes of disharmony. It is concluded that the tradition of hajat lembur in tatar Karang Priangan is a reality of the transfer of knowledge which is structured by considering local ethics andaesthetics.Keywords: hajat lembur, tatar Karang Priangan, transfer of knowledge, local wisdom